MARKETING TRAINING USING INSTAGRAM SOCIAL MEDIA FOR BUFFALO FARMERS - Andi Sukma Indah; Dewi Yuniati; Adli Putra Ermanda; Andi Tenri Darhyati; Lajuk Arif A; Muhammad Yunus Triadi; Ikram Fajrul Ramli; Rani Juita (LPPM Universitas Flores, 2026)
Tandung village has the largest buffalo population in the Tinambung sub-district and in the entire Polewali Mandar district. The 39% increase in buffalo population over the past ten years to 320 buffalo has made the Tinambung sub-district the sub-district with the largest buffalo population in the Polewali Mandar district. The problems farmers face is related to the uncertainty of selling their livestock. When farmers need money, they will first bring some of their livestock to the animal market in North Tana Toraja Regency, which is 94 km from Tandung Village. The farmer will return the sheep to Tandung Village if the livestock is not sold. Farmers also must rent a pick-up truck to transport buffalo cattle or use a car if they are carrying a larger number. Therefore, community service activities were carried out to enable partners to maximise the use of Instagram as a digital marketing medium to help buffalo farmers in Tandung Village market with their livestock. The service activity consists of 4 stages: assessment, training, monitoring and evaluation, and publication. This service activity was carried out on 7 September 2024 in Tandung Village, Tinambung District, Polewali Mandar Regency. This service activity was attended by 32 participants, consisting of service partners, namely members of the Simemangan Livestock Farmer Group, and Field Agricultural Extension Officers (PPL) and village officials. The method used in the training stage is the participatory extension approach, accompanied by demonstrations and practices related to digital marketing. Community service activities at the Simemangan Livestock Farmer Group, Tandung Village, Tinambung District, and Polewali Mandar Regency increased general knowledge about digital marketing, especially using Instagram as a promotional medium. Based on the pre-test and post-test evaluation, it can improve understanding from 44% to 77%.